Results And Discussion of Limnological Study of Ganga River Water of District Haridwar Uttarakhand - Aditi,; Bhatnagar, Ravi (International Journal of Psychosocial Rehabilitation, 2019)
Haridwar is situated on the bank of the Ganga at the foothills of the Shivalik range of mountains that constitute the outer Himalayas. Haridwar city lies at an elevation of 965 feet from the sea level and between latitude 200, 58' N, and longitude 780, 13’ E. The results obtained for the studies made during round the years 2016 and 2017 are presented here (Table 1 to Table 8) A total of 13 physico-chemical parameters were studied as described in the chapter on materials and methods at the selected four sites, namely Sapta Rishi Ghat, Har Ki Pauri, Prem Nagar Ghat and Jatwada Pu